Bioconversion of sago residue into value added products - Awang Adeni, Dayang Salwani; Abd. Aziz, Suraini; Bujang, Kopli; Hassan, Mohd Ali (Academic Journals, 2010)
Bioconversion of the agro-residue offers the possibility of creating marketable value-added products. In this regard, sago residue which contains solid and liquid materials produced abundantly as a byproduct from the sago starch processing industry. Due to its organic nature and low ash content, attempts have been made to produce several products such as fermentable sugar, enzyme, compost for mushroom, animal feed and adsorbent. Utilization of sago residue not only reduce the polluting effects from the sago processing industries, but will also provide an economic solution for waste management system at sago processing mills. This review focuses on the developments in processes and products for the value addition of sago residues through biotechnological means.